Identification of a Single Pair of Interneurons for Bitter Taste Processing in the Drosophila Brain. - Bohra, A.A.; Kallman, B.R.; Reichert, H.; VijayRaghavan, K. (Current Biology, 2018)
Drosophila has become an excellent model system for investigating the organization and function of the gustatory system due to the relatively simple neuroanatomical organization of its brain and the availability of powerful genetic and transgenic technology. Thus, at the molecular and cellular levels, a great deal of insight into the peripheral detection and coding of gustatory information has already been attained. In contrast, much less is known about the central neural circuits that process this information and induce behaviorally appropriate motor output. Here, we combine functional behavioral tests with targeted transgene expression through specific driver lines to identify a single bilaterally homologous pair of bitter-sensitive interneurons that are located in the subesophageal zone of the brain. Anatomical and functional data indicate that these interneurons receive specific synaptic input from bitter-sensitive gustatory receptor neurons. Targeted transgenic activation and inactivation experiments show that these bitter-sensitive interneurons can largely suppress the proboscis extension reflex to appetitive stimuli, such as sugar and water. These functional experiments, together with calcium-imaging studies and calcium-modulated photoactivatable ratiometric integrator (CaMPARI) labeling, indicate that these first-order local interneurons play an important role in the inhibition of the proboscis extension reflex that occurs in response to bitter tastants. Taken together, our studies present a cellular identification and functional characterization of a key gustatory interneuron in the bitter-sensitive gustatory circuitry of the adult fly.